Combinated virtual reality exposure and biofeedback in acrophobia treatment - Maravalhas, Vanessa Cristina Fangueiro (2022)
Acrophobia is the most prevalent type of specific phobia, and its defined according to DSM V as na extreme fear oh heights. It is a chronic dosirder that mau impact people’s lives. The most common therapy used in this condition is cognitive behavior therapy (CBT). This therapy aims to modify non-adaptive cognitions and behaviors, challenging dysfunctional thoughts and beliefs through cognitive and behavioral strategies, including, for exemple, cognitive restructuring and exposure. Through Virtual Reality, as an exposure therapy, i tis possible to obtain a more assertive control of the therapeutic environment, facilitating adaptability and problema solving and offering greater possibilities for customization, flexibility, and controlo f the therapeutic process. This intervention will consist of 16 biweekly evolutions (8 weeks), with each session lasting 50 minutes and structured as follows: Preparation and warm-up of the participant; Personalized and progressive exposure to virtual environments of systematic desensitization; Relaxation and Feedback. The results from both self-report and psychophysiological data revealed a significant reduction in fear of heights in the participants exposed to the exposure therapy program, showing a positive imapct of this protocolo n the treatment of Acrophobia.